Urgensi Peningkatan Kesadaran Keselamatan dan Kesehatan Kerja (K3) bagi Buruh Tani Kelapa Sawit di Kampung Teluk Merempan - Muhammad Alfarezy; Sukamarriko Andrikasmi; Lasmaria Qoretti Simarmata; Zacki Ramadhan; Santi Santi; Yosi Frens Asiska; Ibnu Nurul Abi Al-Asri; Galuh Pramudita; Abdi Julka Nelson; Linda Anna Sari Nasution; Fauziah As Syahidah; Rahmalia Rahmalia (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2025)
Occupational Safety and Health (OSH) is a fundamental right for all workers, including palm oil farm labourers in informal sectors. In Teluk Merempan Village, Mempura District, Siak Regency, palm oil farming is still carried out traditionally without proper OSH practices. This study aims to identify farm workers’ understanding of OSH and to analyze the urgency of legal education as a preventive effort against work-related risks. A descriptive qualitative approach was used, with data collected through observations and in-depth interviews. The findings show that most workers are unaware of their OSH rights, rarely use personal protective equipment (PPE), and have never participated in safety training. The main challenges are low education levels, limited access to labour law information, and entrenched traditional work practices. These results highlight the importance of community-based legal education programs to enhance workers’ legal awareness and OSH implementation in agriculture. As a follow-up, the KUKERTA Team from Universitas Riau designed a local legal education program to support farm workers in improving OSH awareness.